2021
DOI: 10.3904/kjim.2019.118
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of spontaneous coronary artery dissection in young female patients with acute myocardial infarction in Korea

Abstract: Background/Aims We aimed to evaluate the prevalence, characteristics, and clinical outcomes of spontaneous coronary artery dissection (SCAD) in young female patients with acute myocardial infarction (AMI). Methods We identified 8,250 patients diagnosed with AMI who underwent coronary angiogram from the Chonnam National University Hospital database, Gwangju, Korea, between November 2005 and September 2017. A total of 148 female patients aged less than 60 years with a his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In addition, the model relationship between coronary artery lesions and risk factors in young patients with acute myocardial infarction is still uncertain. Smoking and dyslipidemia are major risk factors for AMI, but the new research points out that high-risk occupations such as staying up late and dependence on electronic products may be new risk factors [ 7 ]. Based on this, this study analyzed the clinical data of 150 patients with AMI to explore the location and characteristics of coronary lesions in young patients with AMI during coronary angiography to analyze the relationship between coronary responsibility lesions and left and right coronary advantages, and to reveal possible new risk factors for the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the model relationship between coronary artery lesions and risk factors in young patients with acute myocardial infarction is still uncertain. Smoking and dyslipidemia are major risk factors for AMI, but the new research points out that high-risk occupations such as staying up late and dependence on electronic products may be new risk factors [ 7 ]. Based on this, this study analyzed the clinical data of 150 patients with AMI to explore the location and characteristics of coronary lesions in young patients with AMI during coronary angiography to analyze the relationship between coronary responsibility lesions and left and right coronary advantages, and to reveal possible new risk factors for the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 provides an overview of the characteristics of the 34 included studies 2,4‐6,11‐40 . The mean duration of follow‐up was 33 ± 20 months.…”
Section: Resultsmentioning
confidence: 99%
“…I immediately read with great attention and interest the significant and well-presented article recently published in an issue of this journal by Kim et al [1] entitled "Clinical characteristics of spontaneous coronary artery dissection in young female patients with acute myocardial infarction in Korea." They evaluated the prevalence, characteristics, and clinical outcomes of spontaneous coronary artery dissection (SCAD) in young female patients with acute myocardial infarction in Korea.…”
mentioning
confidence: 99%
“…Although various potential risk factors for SCAD have been evaluated in the study of Kim et al [1], the influence of hormone has not. However, clinical data have demonstrated that patients under either oral contraceptive use or hormone replacement therapy have an increased risk for developing SCAD.…”
mentioning
confidence: 99%
See 1 more Smart Citation